Q: What is 5a - 1 plus a equals 11?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

6a + 5a = -11 11a = -11 a = -11/11 = -1

5a + 2 = 7 subtract 2 from both sides: 5a = 5 divide both sides by 5: a = 1

2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1

So we have 5a + 11 + 3a - 7 = -4 Start by combining common terms such as the 5a and 3a to give you 8a and 11 and -7 to give you 4. So now your equation is 8a + 4 = -4. Subtract 4 from both sides gives you 8a = -8. Divide -8 by 8 to give you a = -1, your solution.

Redefine "plus".

Related questions

If: 5a-1+a = 11 Then: a = 2

6a + 5a = -11 11a = -11 a = -11/11 = -1

6a + 5a = -11 Combining like terms: 11a = -11 Dividing by 11: a = -1

Answer to: 5a + 1 = a - 3a = -1

If: 2a+13 = 5a+1 Then: a = 4

5a = -5a + 5Add 5a to each side:10a = 5Divide each side by 10:a = 5/10 = 1/2

No it equals 2 10 plus 1 equals 11

5a + 2 = 7 subtract 2 from both sides: 5a = 5 divide both sides by 5: a = 1

2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1

So we have 5a + 11 + 3a - 7 = -4 Start by combining common terms such as the 5a and 3a to give you 8a and 11 and -7 to give you 4. So now your equation is 8a + 4 = -4. Subtract 4 from both sides gives you 8a = -8. Divide -8 by 8 to give you a = -1, your solution.

If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1

5a(2b + 1)